PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA MELALUI KEPEMIMPINAN DEMOKRATIS (Studi Empiris pada Perangkat Desa di Kabupaten Pemalang) - hendratno hendratno (Universitas 17 Agustus 1945 Semarang, 2026)
This study aims to analyze the influence of competence and work discipline on the performance of village officials, with democratic leadership as an intervening variable in Pemalang Regency. The research is motivated by inconsistencies in prior empirical findings and the persistent phenomenon of administrative reporting delays despite a noted increase in the number of self-sufficient villages. The theoretical framework employed is Vroom's Expectancy Theory, which posits that performance is shaped by expectancy, instrumentality, and valence. The research population comprised all village officials in Pemalang Regency, with the sample determined using the Slovin formula through stratified proportional random sampling. Data were collected via a Likert-scale questionnaire and analyzed using Partial Least Square (PLS) with SmartPLS software. The findings reveal that competence and work discipline each exert a positive and significant effect on both performance and democratic leadership. Democratic leadership is likewise proven to have a positive and significant effect on performance, while simultaneously mediating the influence of competence and work discipline on performance. Collectively, competence and work discipline account for a substantial proportion of the variance in both democratic leadership and village official performance. This study contributes to the development of a democratic leadership mediation model within the context of village governance and offers practical recommendations, including the enhancement of digital competencies, the strengthening of reward-punishment systems, the optimization of village deliberation forums, and improvements in the delegation of authority and information transparency.